If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-41=-2(-2x-7)-6x
We move all terms to the left:
3x-41-(-2(-2x-7)-6x)=0
We calculate terms in parentheses: -(-2(-2x-7)-6x), so:We get rid of parentheses
-2(-2x-7)-6x
We add all the numbers together, and all the variables
-6x-2(-2x-7)
We multiply parentheses
-6x+4x+14
We add all the numbers together, and all the variables
-2x+14
Back to the equation:
-(-2x+14)
3x+2x-14-41=0
We add all the numbers together, and all the variables
5x-55=0
We move all terms containing x to the left, all other terms to the right
5x=55
x=55/5
x=11
| -7y+7(1+2y)=-2y-11 | | (1/2)h-12=-5 | | -8-3(44-5y)=-2y+13 | | 6p+4/6=4p-83 | | 20×x=50 | | -2k-25=2(-4k-39)-1 | | -2x-15=10-2x-25 | | 4^2+20x=0 | | 8n=–6+7n | | 5+7x=-128 | | 7(-3y-5)+9=-8y | | 9x=5x+4(2x-13) | | -10a-24(5a+48)=-2a | | -5+24=-8t-15 | | 11=10(3a+31)+1 | | 3^(2x-3)=4^x | | 12=4(4y-18)-9y | | -43(3z-35)-5=-4z | | (3x-1)(2x-9)=90 | | 8(1)+2y=-6 | | 2(2x-6)-8=4(3x-2) | | 9x-18=5x-2 | | 2b-3b=+4b | | s=0.8(24) | | 6912=(18x+6x)*18x | | 3x^2+6x+2=4 | | b=(0.75)90 | | 10.1x-1.6x+44=7 | | x+5x-5+5x-5=122 | | 6−9x=-120 | | x+2x-3+2x-3=34 | | 30*30=40x*10x |